Analisis Kesulitan Guru Dalam Implementasi Kurikulum Merdeka Di Taman Kanak- Kanak Pesat Jawa - Gea, Jeni Juniarwati; Romini, Romini (EDULEAD: Journal of Christian Education and Leadership, 2024)
Abstract: Curriculum is an approach that instructs schools to achieve educational goals. This study aims to analyze the obstacles faced by PESATJawa Kindergarten (TK) in the Implementation of the Independent Curriculum. Four Rapid Kindergartens in Java are: Integrated Pniel Christian Kindergarten, Sion Tri Damarsari Christian Kindergarten, Integrated Immanuel Christian Kindergarten and Integrated Love Seed Kindergarten. This study used a qualitative descriptive method. Data collection was conducted through interviews and observations. Each educational organization or foundation has different capabilities. The obstacles and difficulties faced by each institution include: still need to practice and make habituation in developing the skills of giving provocation words, expressing open questions, and the need for teacher creativity in facilitating diverse games. As a result, teachers have difficulty in developing games that are by-play activities in the center. The strategy that every educator needs to do is to reflect after teaching to increase understanding of the Independent Curriculum and educators seek to attend workshops and training on the Implementation of the Independent Curriculum Paud. So that the independent curriculum can be implemented in the learning model of the Center.Abstrak: Kurikulum merupakan pendekatan yang mengintruksikan sekolah untuk mencapai tujuan pendidikan. Penelitian ini bertujuan menganalisis tentang kendala yang dihadapi oleh Taman Kanak-kanak (TK) PESAT Jawa dalam Implementasi Kurikulum Merdeka. Empat TK Pesat di Jawa yaitu: TK Kristen Pniel Terpadu, TK Kristen Sion Tri Damarsari, TK Kristen Immanuel Terpadu dan TK Benih Kasih Terpadu. Penelitian ini menggunakan metode deskriptif kualitatif. Pengumpulan data dilakukan melalui wawancara dan observasi. Setiap organisasi atau Yayasan pendidikan memiliki kemampuan yang berbeda. Kendala dan kesulitan yang dihadapi setiap lembaga antara lain: masih perlu berlatih dan melakukan pembiasaan dalam mengembangkan keterampilan memberikan kata-kata provokasi, mengungkapkan pertanyaan terbuka dan perlunya kreativitas guru dalam memfasilitasi permainan yang beragam. Akibatnya guru mengalami kesulitan dalam mengembangkan permainan yang sesuai dengan kegiatan main di sentra. Strategi yang perlu dilakukan setiap pendidik ialah melakukan refleksi setelah mengajar untuk meningkatkan pemahaman tentang Kurikulum Merdeka dan pendidik mengupayakan mengikuti workshop maupun pelatihan tentang Implementasi Kurikulum Merdeka Paud. Sehingga kurikulum merdeka dapat diimplementasikan pada pembelajaran model Sentra.